In vivo Assessment of Human Brainstem Cerebrovascular Function: A Multi-Inversion Time Pulsed Arterial Spin Labelling Study. Issue 6 (June 2014) - Warnert, Esther AH; Harris, Ashley D; Murphy, Kevin; Saxena, Neeraj; Tailor, Neeta; Jenkins, Nigel S; Hall, Judith E; Wise, Richard G
The brainstem (BS) is involved in critical physiologic processes, including control of cardiovascular and respiratory functions. This study implements a multi-inversion time pulsed arterial spin labelling (MTI PASL) imaging sequence that addresses the challenges of BS imaging and aims to measure normal and elevated BS perfusion in healthy volunteers. An initial experiment was performed to obtain the kinetic curve of the label in the BS and consequently to estimate the label arrival times and tissue perfusion in seven participants. A second experiment estimated the BS cerebral vascular reactivity (CVR) to hypercapnia in 10 participants. Images were acquired with a gradient-echo sequence with two spiral interleaves and short echo time (TE = 2.7 ms). Data were analyzed with a two-compartment model, including a tissue and arterial component. In both experiments, perfusion in the BS was significantly lower than in cortical gray matter (repeated measures analysis of variance (RM-ANOVA), P <0.05), which is as expected since the BS consists of gray and white matter, the latter typically showing lower perfusion. The BS CVR found here is comparable to previous reports obtained with positron emission tomography (PET) imaging. Multi-inversion time pulsed ASL in combination with a two-compartment signal model can be used to assess BS perfusion and CVR.